Beneficios ambientales de las áreas arboladas en las calles colindantes al aeropuerto viejo en los residentes de Iquitos. Loreto 2024 - Leonardo Garcia, Sachy Shantall (2025)
The study, with a descriptive, analytical and transversal approach, aimed to analyze the social perception of the benefits of environmental services provided by tree-lined areas on streets 30 de Agosto (2,3,4, and 5 blocks) and Sargento Lores (12,12, 14, and 15 blocks) from Iquitos . With a sample of 60 residents selected through intentional sampling, a structured survey was applied with a Cronbach's Alpha reliability of 0.789. Data normality was assessed with the Kolmogorov-Smirnov test and Spearman correlation was used for inferential analysis. The results showed that residents positively value the environmental benefits of urban trees, highlighting the improvement in air quality, thermal regulation and landscape beautification. Likewise, it was identified that the social perception of these services is influenced by the level of knowledge, the maintenance of green areas and community participation in their conservation. Significant differences were observed in the valuation of ecosystem services based on residents' proximity to wooded areas, highlighting the need to integrate accessible green spaces into urban planning. The correlation between the perception of environmental benefits and the factors that influence their valuation suggests that the recognition of these services is associated with a greater appreciation of maintenance, information and citizen participation. These findings highlight the importance of conservation and awareness strategies to strengthen the management of green areas in the city.